Exploring Mars - Parks, Peggy J. 1951-; Gale Group; SpringerLink (Online service). (Detroit, Mich. Lucent Books, 2005)
Discusses the Red Planet, early observations and beliefs, and future exploration.
The mysterious red planet -- Early observations and beliefs -- An earth-like world -- The space race -- An era of discovery -- Mars in the future.
Electronic reproduction.
Keywords: Electronic books; Mars (Planet) -- Exploration